RESPON MORFOLOGI, BIOMASSA, DAN KANDUNGAN KLOROFIL DAUN MIMOSA AIR (Neptunia oleracea L.) PADA AIR YANG TERPAPAR MERKURI KLORIDA (HgCl2) - Fadhlullah, Hafizh Rizqi; Wardoyo, Elvi Rusmiyanto Pancaning; Zakiah, Zulfa (Jurnal Protobiont, 2020)
Water mimosa (Neptunia oleracea L.) is one of the aquatic plants (Leguminoceae) which had adaptive capabilities on water environment was exposed by heavy metal. This research purposed to know the morphology responses, biomass and chlorophyll contents of water mimosa (Neptunia oleracea L.) in water exposed by HgCl2. This research used Completely Randomized Designed (CRD) with 4 levels of HgCl2 treatment such as: control (A), 75 ppm (B), 150 ppm (C), and 225 ppm (D). The experimental plants used was N. oleracea L. from the treatment of HgCl2 concentrations give effects on morphology, biomass and chlorophyll contents, such as: chlorophyll a, chlorophyll b, total chlorophyll. N. oleracea showed the change of color, leaves become yellow, stems are thinner, brownish-look root with soft textures and curled up. The concentration of HgCl2 225 ppm, biomass of N. oleracea L, occurred decrease until 81.93%, and chlorophyll contents of N. oleracea L. occurred decrease until 93.11%.